Rates and factors for 30-day readmission in patients with substance use disorders during the COVID-19 pandemic - Ssentongo, Paddy; Nunez, Jonathan; Dissinger, Donald; Bali, Bhavna (Frontiers in Psychiatry, 2025)
BackgroundSubstance use disorders (SUD) are associated with frequent hospitalizations, premature discharge, and high rates of early readmission. The COVID-19 pandemic further disrupted the continuity of addiction care, heightening the vulnerability of hospitalized patients. Identifying inpatient factors linked to reduced 30-day readmission may guide strategies to improve post-discharge outcomes in this population.MethodsWe conducted a retrospective cohort study of adults with SUD admitted to Penn State Health Hershey Medical Center between 1 January and 30 December 2021, who received addiction medicine consultations. Demographic, social, and clinical characteristics were extracted from the electronic health records. Logistic regression was used to assess the associations between addiction interventions, including educational counseling, pharmacotherapy initiation, and other referrals, and 30-day all-cause readmission, adjusting for age, sex, marital status, insurance, and comorbidities.ResultsAmong 561 patients (mean age, 42 years; 62% men), 139 (25%) were readmitted within 30 days. Depression or anxiety was present in 44% of the patients, and 42% reported polysubstance use. Single marital status and the presence of one or more comorbidities were independently associated with higher odds of readmission (adjusted odds ratio [aOR], 2.82; 95% CI, 1.45–5.52; P = .002, and aOR, 2.41; 95% CI, 1.06–5.45; P = .035, respectively). Compared with those who declined assistance, patients who received educational counseling had significantly lower odds of readmission (aOR, 0.53; 95% CI, 0.31–0.90; P = .02), and those who were initiated on addiction-related medications showed a nonsignificant trend toward reduced risk (aOR, 0.62; 95% CI, 0.32–1.21; P = .16). In contrast, patients who experienced a self-directed discharge had more than threefold higher odds of readmission (aOR, 3.02; 95% CI, 1.36–6.73; P = .007).ConclusionIn this cohort of hospitalized patients with substance use disorders, inpatient addiction interventions were associated with significantly lower 30-day readmission rates. Educational counseling and pharmacotherapy initiation reduced readmission risk, whereas self-directed discharge was associated with markedly higher odds of readmission. These findings support the integration of structured addiction consultation services to improve post-discharge outcomes and reduce preventable hospitalizations.